Turbidity removal and pH of raw water treated with natural coagulants - Cunha, Rayanna Pinheiro; Thebaldi, Michael Silveira; Silva, Yasmin Fernandes; Franco, Camila Silva; Diotto, Adriano Valentim (Revista em Agronegócio e Meio Ambiente, 2023)
Concerns regarding water pollution and scarcity have led researchers to investigate new sustainable water treatment technologies, such as the use of natural coagulants, that can be used for water treatment in decentralized locations at small rural communities, as these materials can be used in compact water treatment plants. Thus, the present study evaluated the use of natural coagulants, drumstick tree seeds and tannins extracted from black acacia, in water treatment to remove turbidity. To determine the ideal coagulant dosage, jar tests were performed, followed by filtration to remove the formed sludge. pH and turbidity were analyzed to compare the coagulants efficiency. The natural coagulants achieved satisfactory removal of suspended solids, completely removed turbidity, and causing no significant changes in pH, unlike aluminum sulfate, hence, these natural materials can be used as an alternative to chemical coagulants.